2005
DOI: 10.1080/09583150500136444
|View full text |Cite
|
Sign up to set email alerts
|

Host specificity testing and suitability of a European biotype of the braconid parasitoidMicroctonus aethiopoidesas a biological control agent againstSitona lepidus(Coleoptera: Curculionidae) in New Zealand

Abstract: The European biotype of the parasitoid Microctonus aethiopoides Loan (Hymenoptera: Braconidae) is being considered for release against Sitona lepidus Gyllenhal (Coleoptera: Curculionidae) in New Zealand. Host specificity was evaluated in the laboratory using both endemic and introduced weed biological control curculionid species, with 12 no-choice and three choice experiments carried out comparing the S. lepidus and test weevils. Two further no-choice tests used the Moroccan M. aethiopoides biotype to compare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…The search for candidate biological control agents for S. lepidus commenced in Europe and North America in 1998 (Phillips et al 2000) and extensive testing in quarantine (Goldson et al 2005) resulted in a thelytokous Irish strain of Microctonus aethiopoides Loan (Hymenoptera: Braconidae) being approved for release in New Zealand by the Environmental Risk Management Authority under the Hazardous Substances and New Organisms Act 1996 . This species lays eggs in the abdomen of adult weevils and renders host females sterile.…”
Section: Introductionmentioning
confidence: 99%
“…The search for candidate biological control agents for S. lepidus commenced in Europe and North America in 1998 (Phillips et al 2000) and extensive testing in quarantine (Goldson et al 2005) resulted in a thelytokous Irish strain of Microctonus aethiopoides Loan (Hymenoptera: Braconidae) being approved for release in New Zealand by the Environmental Risk Management Authority under the Hazardous Substances and New Organisms Act 1996 . This species lays eggs in the abdomen of adult weevils and renders host females sterile.…”
Section: Introductionmentioning
confidence: 99%
“…Although the evidence is less extensive, VLP were not observed during examination of ovary tissues in M. aethiopoides from other locations in Europe and Norway. Containment studies have predicted that the potential host range of the Irish biotype, now approved for release in New Zealand, will be narrower than that of the existing Moroccan biotype (Goldson et al, 2005). It is possible that the absence of MaVLP in the Irish biotype might be a factor in its apparent reduced host range capability.…”
Section: Discussionmentioning
confidence: 98%
“…Quarantine tests with native New Zealand test species have suggested that the host range proWle of the European biotypes was diVerent from the Moroccan biotype already present in NZ (Goldson et al, 2005), and so the objective of this TEM study was to determine the presence (or absence) and ultrastructure of VLP in the Irish biotype for comparison with the Moroccan biotype. Specimens from France, Wales, and Norway were also examined, since these were available in quarantine as part of the S. lepidus biological control programme.…”
Section: Introductionmentioning
confidence: 99%
“…A number of Weld and laboratory studies have shown that elevated CO 2 promotes N 2 Wxation in T. repens Newton et al 1994;Zanetti et al 1996;Manderscheid et al 1997) when nutrients such as phosphorus are not limiting (Edwards et al 2006). The clover root weevil (Sitona lepidus Gyllenhal), is a signiWcant pest of T. repens in northern temperate regions, and has most recently become a serious problem in New Zealand (Goldson et al 2005). The adult feeds on leaves and reproduces sexually aboveground, where female S. lepidus lay eggs either on or around the base of the plant, giving rise to larvae which then burrow into the soil and attack the root system.…”
Section: Introductionmentioning
confidence: 99%